Thermo-hydro mechanical densification process of Nothofagus pumilio and Nothofagus antarctica and the effect of annual width ring on modulus of hardness, and dynamical mechanical properties - Pečnik, Jaka Gašper; Schwarzkopf, Matthew; Kutnar, Andreja (Zenodo, 2018)
Conference abstract for Final COST Action FP1407 International Conference - Living with modified wood : Pages 96-97